IoT Framework Current Trends and Recent Advances to Management Company in The PT.TNC - Teddy Surya Gunawan; B Herawan Hayadi; Cindy Paramitha; Muhammad Sadikin (STMIK Pontianak, 2020)
The Internet of Things (IoT) is a fast growing and user-friendly technology that connects everything together. And it can communicate effectively between the people who connect